Improving Organizational Sustainability of an Urban Indian Health Clinic With an Innovative Pharmacy Model - Noah Gallegos; Leah Fitzgerald; Alex Versackas; Erica Sherer; Connie Valdez (SAGE Publishing, 2022)
Introduction: To increase access to care for the urban American Indian population, a collaboration was developed between an Urban Indian Health Clinic (UIHC) and Federally Qualified Healthcare Center (FQHC) to reduce financial barriers, increase patient access to affordable medications, and augment the integrated model of care. Objective: To describe the design and implementation of an innovative pharmacy model through a partnership between an UIHC and a FQHC. Methods: A collaborative partnership between an UIHC and a FQHC was developed to spread scarce 340B federal resources as a method to enhance patient care. The innovative practice model included the development of processes to (1) increase medication access to all patients by providing access to affordable medications at clinic and the provision of mail order services, (2) minimize program expenses through cost-sharing of a pharmacist salary, (3) expand clinical pharmacy programs (collaborative drug therapy management) to augment integrated patient care, and (4) optimize 340B cost savings for the clinic by establishing contracts and implementing adjudication software to obtain medication reimbursement from Medicaid and other third party insurances. Results: Through the cost-sharing of a pharmacist salary and use of remote verification, the majority of prescription medications were available to patients at the UIHC through implementation and expansion of an other outlet. Collaborative drug therapy management (CDTM) protocols were successfully implemented which allowed clinical pharmacy services to collaboratively manage chronic conditions. All adult primary care providers adopted the integrated patient care model. Third-party pharmacy insurance contracts were obtained and computer software was installed to allow for the adjudication of pharmacy claims, resulting in cost savings from medication reimbursement. Conclusion: The innovative collaborative partnership between an UIHC and an FQHC demonstrated how scarce federal resources can be leveraged using the 340B program to increase patient access to affordable medications. This innovative model reduced financial barriers to the clinic, and allowed for expansion of pharmacist led CDTM programs and augmentation of integrated clinical services. The cost savings observed from this novel program additionally fueled programmatic sustainability through reinvestment into the pharmacy program and is expected to continue to fund the program in the future.